Evolution of the intracranial features of congenital cytomegalovirus on MRI. Issue 5 (May 2023) - Garnham, J.; Gaur, P.; Basheer, N.; Lyall, H.; Jan, W.; Kachramanoglou, C.
Abstract : Aim: To describe the evolution of the intracranial features of congenital cytomegalovirus (cCMV) on magnetic resonance imaging (MRI). Materials and methods: Sixteen infants with polymerase chain reaction (PCR)-confirmed cCMV who had undergone at least two MRI examinations of the brain were identified. Two paediatric neuroradiologists reviewed the baseline studies retrospectively for intracranial features of cCMV, including white matter signal abnormalities, subependymal cysts, malformations of cortical development, and intracranial calcification. The subsequent MRI studies were then reviewed and directly compared to the baseline examinations. Results: White matter signal abnormalities were seen on all 16 baseline studies (100%); these persisted on all subsequent examinations but were patchier, more focal, and associated with an interval reduction in white matter volume. Subependymal cysts were present on 11 (69%) of the baseline scans; these almost universally regressed (in 10 of the 11 cases [91%]), with no new cysts appreciable on subsequent imaging. Malformations of cortical development, exclusively in the form of polymicrogyria, were seen in six (38%) patients and persisted, unchanged, on subsequent imaging. Intracranial calcification was seen in a minority of baseline studies (4 [25%]) and remained stable on subsequent scans. Conclusion: Children with cCMV who present later in life without an established or suspected underlying pathology can pose a challenge to the assessing radiologist. The radiological sequelae of cCMV can be non-specific; in some cases, white matter signal abnormalities and focal loss of white matter volume may be the only intracranial features. It is therefore important that radiologists are aware of cCMV as a potential differential for these findings. Highlights: White matter signal abnormalities in cCMV become patchier over time. There is an associated reduction in white matter volume on subsequent scans. Subependymal cysts tend to regress. Structural malformations and intracranial calcification persist, unchanged. White matter signal abnormalities and focal volume loss can be the only features.